Changing pattern and safety of pretransplant malignancy in kidney transplant recipients - Tae Hyun Ban; Woo Yeong Park; Kyubok Jin; Seungyeup Han; Byung Ha Chung; Sun Cheol Park; Bum Soon Choi; Cheol Whee Park; Sang-Seob Yun; Yong-Soo Kim; Chul Woo Yang (The Korean Society of Nephrology, 2019)
Background : Cancer rates are increasing not only in the general population but also in patients with end-stage renal disease. We investigated the changing pattern of pretransplant malignancy in kidney transplant recipients over 5 decades.Methods : We reviewed 3,748 kidney transplant recipients between 1969 and 2016. We divided patients into three groups (1969-1998, 1999-2006, 2007-2016) based on the era of the cancer screening system used throughout the nation. We analyzed the incidence and pattern of pretransplant malignancy among the three groups. We also evaluated recurrent and de novo malignancy in these patients compared to patients without pretransplant malignancy.Results : A total of 72 patients exhibited pretransplant malignancy (1.9%). There were no cases of pretransplant cancer until 1998, but the rate of pretransplant malignancy gradually increased to 1.1% during 1999-2006 and further increased to 4.3% thereafter. The most frequent types of pretransplant malignancy changed from the bladder, liver, and stomach cancers to thyroid cancer and renal cell carcinoma. There were no de novo cases, but there were three cases of recurrent cancer in patients with pretransplant malignancy; the recurrence rate among kidney transplant recipients with pretransplant malignancy was not significantly different from the incidence rate of de novo malignancy among kidney transplant recipients without pretransplant malignancy (4.2% vs. 6.9%, P = 0.48).Conclusion : The incidence of pretransplant malignancy in kidney transplantation candidates is gradually increasing, and recent increases were accompanied by changes in cancer types. Pretransplant malignancy may not be a hindrance to kidney transplantation because of the low incidence of posttransplant recurrence and de novo malignancy.